2019
DOI: 10.1159/000504623
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endothelin and Endothelin Antagonists in Chronic Kidney Disease

Abstract: <b><i>Background:</i></b> Endothelins (ET) are a family of peptides that act as potent vasoconstrictors and pro-fibrotic growth factors. ET-1 is integral to renal and cardiovascular pathophysiology and exerts effects via autocrine, paracrine and endocrine signaling pathways tied to regulation of aldosterone, catecholamines, and angiotensin. In the kidney, ET-1 is critical to maintaining renal perfusion and controls glomerular arteriole tone and hemodynamics. It is hypothesized that ET-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 97 publications
1
52
0
3
Order By: Relevance
“…Although most of clinical ER antagonists were highly selective ETA-R blockers, high dosages of such medicine could still block ETB-Rs[ 9 ]. Inhibition of the ETB-R in tubular cells also causes activity of Na + and water transport[ 4 ]. Anemia may ascribe to hemodilution due to fluid retention[ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although most of clinical ER antagonists were highly selective ETA-R blockers, high dosages of such medicine could still block ETB-Rs[ 9 ]. Inhibition of the ETB-R in tubular cells also causes activity of Na + and water transport[ 4 ]. Anemia may ascribe to hemodilution due to fluid retention[ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the kidneys, endothelin-1 (ET-1) exerts several physiological effects, including control of water and sodium homeostasis. The ET system is complicated, consisting of a converting enzyme and two active receptors: The ETA (ETA-R) and ETB (ETB-R) receptors[ 4 ]. The activation of ETA-Rs mainly in vascular smooth muscles causes extremely potent vasoconstriction, endothelial dysfunction, insulin resistance, inflammation, and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies in diabetic nephropathy, hypertensive kidney disease, and focal segmental glomerulosclerosis demonstrated that ET-1 inhibition can reduce proteinuria and improve kidney function ( 46 ). In a randomized clinical trial that tested avosentan, an ET-1A inhibitor, against placebo was ended prematurely after 4 months due to an increase in cardiovascular events in the avosentan arm, mainly due to fluid overload and congestive heart failure ( 30 ).…”
Section: Endothelin Antagonistsmentioning
confidence: 99%